Makna Kata Hari (Yom) Dalam Ayub 3:1-10 - Bastanta Pradhana Bangun (Sekolah Tinggi Teologi Sriwijaya, 2022)
Abstract: This paper discusses the understanding and meaning of the day (yom) according to Job 3:1-10. The purpose of this research is to enrich the approach and interpretation of the interpretation of the Book of Job and open a new understanding which in the future is expected to have an impact on spiritual needs Christians are facing challenges in life that are increasingly difficult or complex, namely to see a new nuance of the relational relationship between humans and God. To achieve this, the main issues discussed in this paper are: how and to what extent does Job 3: 1-10 interpret the word